Economic psychology - Ranyard, Rob (Hoboken : Wiley-Blackwell, 2017)
'A comprehensive overview of contemporary economic psychology Economic Psychology presents an accessible overview of contemporary economic psychology. The science of economic mental life and behavior is increasingly relevant as people are expected to take more responsibility for their household and personal economic decisions. The text will, in addition to reviewing current knowledge on each topic presented, consider the practical and policy implications for supporting economic decision making. Economic Psychology examines the central aspects of adult decision making in everyday life and includes the theories of economic decision making based on risk, value and affect, and theories of intertemporal choice. The text reviews the nature and behavioral consequences of economic mental representations about such things as material possessions, money and the economy. The editor Robert Ranyard-a noted expert on economic psychology-presents a life-span developmental approach, from childhood to old age. He also reviews the important societal issues such as charitable giving and economic sustainability. This vital resource: Reviews the economic psychology in everyday life including financial behaviour such as saving and tax-paying and matters such as entrepreneurial activity Offers an introduction to the field and traces the emergence of the discipline, from Adam Smith to George Katona and Herbert Simon Includes information on societal issues such as charitable giving and pro-environmental behaviour Considers broader perspectives on economic psychology: life-span psychological development from childhood to old age Written for students of psychology, Economic Psychology reviews the most important information on contemporary economic psychology with a focus on individual and household economic decision making, ranging widely across financial matters such as borrowing and saving, and economic activities such as buying, trading, and working.'--
'This book presents an accessible overview of contemporary economic psychology. The science of economic mental life and behavior is increasingly relevant as people are expected to take more responsibility for their household and personal economic decisions. The text will, in addition to reviewing current knowledge on each topic presented, consider the practical and policy implications for supporting economic decision making'--
Machine generated contents note: Contents Preface Acknowledgements List of Contributors Part I: Fundamentals 1. Introduction to Economic Psychology: The Science of Economic Mental Life and Behaviour Rob Ranyard and Vera Rita de Mello Ferreira Theories of Economic Decision Making: Risk, Value and Affect Anton Kuhberger and Michael Schulte-Mecklenbeck Future-oriented Decisions: Intertemporal Choice Daniel Read and Marc Scholten Part II: Research Methods Research Methods for Economic Psychology Gerrit Antonides Assessing Psychological Dispositions and States That Can Influence Economic Behaviour Simon McNair and W. Ray Crozier Developing, Evaluating and Using Subjective Scales of Personality, Preferences, and Well-Being: A Guide to Psychometrics for Psychologists and Economists Alex M. Wood and Christopher J. Boyce Part 3: Economic Mental Representations The Psychological Meaning of Money Tomasz Zaleskiewicz, Agata Gasiorowska, and Kathleen D. Vohs Mental Accounting and Economic Behaviour Gerrit Antonides and Rob Ranyard How Laypeople Understand Economics David Leiser and Zeev Kril The Citizen's Judgments of Prices And Inflation Rob Ranyard, Fabio Del Missier, Nicolao Bonini and Davide Pietroni Materialism and The Meaning of Possessions W. Ray Crozier Part 4: Financial Behaviour Defining and Influencing Financial Capability Ivo Vlaev and Antony Elliott Saving Behaviour: Economic and Psychological Approaches Ellen K. Nyhus The Psychology of Borrowing and Over-Indebtedness Rob Ranyard, Sandie McHugh and Simon McNair Behaviour in Financial Markets Martin Hedesstrom Tax Behaviour Erich Kirchler and Erik Hoelzl Part 5: Economic Activity Motivations to Volunteer Bruno S. Frey and Jana Gallus Entrepreneurial Activity Artur Domurat and Tadeusz Tyszka The Economic Psychology of Gambling Juemin Xu and Nigel Harvey Part 6: Life-span perspectives Economic Socialization: Childhood, Adolescence, and Early Adulthood Annette Otto and Joyce Serido Childhood Psychological Predictors of Lifelong Economic Outcomes Mark Egan, Michael Daly and Liam Delaney The Economic Psychology of Financial Decision Making and Money Management in the Household Stefanie J. Sonnenberg Ageing and Economic Decision Making Wandi Bruine de Bruin Part 7: Economic Psychology and Society Psychological Determinants of Charitable Giving Ilana Ritov and Tehila Kogut Life Satisfaction and Emotional Well-Being: Psychological, Economic and Social Factors Tommy Garling and Amelie Gamble Living in Poverty: Understanding Financial Behaviours in Vulnerable Groups Cazilia Loibl Economic Psychology and Pro-Environmental Behaviour Michel Handgraaf,Anouk Griffioen, Jan Willem Bolderdijk and John Thøgersen Insurance Behaviour and Society Rob Ranyard, John Ashton and Bill Hebenton Index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Economics -- Psychological aspects; BUSINESS & ECONOMICS / Consumer Behavior; Economics -- Psychological aspects; BUSINESS & ECONOMICS / Economics / General; BUSINESS & ECONOMICS / Reference; Electronic books